Relationship between electronic structures and antiplasmidial activities of xanthone derivatives: A 2D-QSAR approach - KPOTIN, ASSONGBA GASTON; Bédé, Affoué Lucie; KPOTA HOUNGUE, MAHOUGBE TATA ALICE; ANATOVI, Wilfried (My University, 2019)
Malaria is an important disease causing many death in several countries of Africa and Asia. In these continents, some plants such as Garcinia cola are used to fight against this disease because they contain xanthone derivatives which present antiplasmodial activity. The present theoretical study aims to establish a relationship between the electronic structure and the antiplasmodial activity of some xanthone derivatives, and more specifically to build a 2D-pharmacophore model in order to predict the biological activity of xanthone derivatives. The calculations are performed within the density functional theory (DFT) using the B3LYP/6- 31G(d,p) level of theory. The developed approach quantitative structure-activity relationship (QSAR) follows the Klopman- Peradejordi-Gómez (KPG) methodology. We obtain a statistically significant equation relating the variation of the logarithm of half maximal inhibitory concentration (log(IC50)) with the variation of the numerical values of a set of eight local atomic reactivity descriptors (R = 0.98, R2 = 0.97, adj-R2 = 0.95, F(8.13) = 48.63, p < 0.00000, SD 0.08). The antiplasmodial activity seems to be driven by atomic orbitals and charges. Our 2D-pharmacophore model should be useful to propose new xanthone derivatives with higher antiplasmodial activity.
Keywords: Xanthone . Antiplasmodial . QSAR . DFT . Klopman-Peradejordi-Gómez approach . Malaria